Seasonal dynamics of fine root length in European beech: unveiling unexpected winter peaks and summer declines - Aron Garthen; Kirsten Brandt; Marcin Klisz; Andrey V. Malyshev; Bo Peters; Robert Weigel; Juergen Kreyling (Oecologia, 2025)
Fine roots play a crucial role in many ecological and biogeochemical processes in temperate forests. Generally, fine root biomass is expected to increase during the growing season, when water and nutrient demands are high, but information on seasonal variability is still scarce. Here, seasonal differences in root length of European beech ( Fagus sylvatica L.) were analysed at eight sites within its north-eastern distribution range. Fine roots of mature trees were monitored using minirhizotrons. Scans were taken for three different depths at the beginning of winter, the end of winter and over the summer for two consecutive years, and analysed automatically by an AI-algorithm (RootDetector). An additional experiment was carried out to show that the RootDetector was unaffected by changes in soil moisture. Root-length density was 40% higher at the beginning of winter and 51% higher at the end of winter than in summer. Our results indicate a net root loss during adverse conditions in early summer, but no trend towards deeper root growth over these drier periods. Interestingly, the root loss was compensated afterwards during more favourable conditions in autumn. We could show that fine root length in temperate forests is seasonally more variable and, so far, less predictable than previously assumed. A profound understanding of this seasonal variability is important for modelling terrestrial biogeochemical processes and global carbon fluxes.